Use of prostaglandin synthetic analogue E1 for uterus cervix preparation and labor induction - I. D. Yevtushenko; A. Sh. Makhmutkhodzhayev; T. V. Ivanova; O. V. Parshina; I. A. Ryzhova; T. I. Kufareva; V. N. Popova (Бюллетень сибирской медицины, 2003)
A clinical prospective examination of 90 women with complete pregnancy and indications for labor induction because of unsatisfactory maturity of uterus cervix has been made. The aim was to create a comparative analysis of efficiency of intravaginal introduction of prostaglandin synthetic analogue E1 misoprostol («Sytotec») and intracervical introduction of prostaglandin E2 dinoprostone («Prepidil» gel) for uterus cervix preparation and labor induction at complete pregnancy. Misoprostol in a dose of 25 mkg has been introduced to pregnant women of the 1 group (n=44), every 4 hours not more than 3 times. In case of discharge of waters or labor activity the second introduction has not been done. Dinoprostone has been introduced intracervically in a single dose to pregnant women of the 2 group (n=46). The use of misoprostol has been accompanied by spontaneous beginning of labor activity by 2 times more often than the use of dinoprostone. The quantity of vaginal births within 12 and 24 hours of observation has been surely greater and the duration of time between the beginning of introduction and labor has been surely smaller in the group of women received misoprostol as compared to the one received dinoprostone. It has not been revealed any differences between examined groups by the frequency of uterus hyperstimulation symptom development, labor duration, frequency of abdominal and vaginal labor, as well as perinatal outcomes.